Essays on Forced Migration and Civil Conflict - Turkoglu, Oguzhan (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2021)
This thesis examines the effect of conflict dynamics and rebel groups on forced migration. More specifically, it analyzes how insurgent groups impact displacement flows, decisions to flee, and attitudes toward refugees. To test its argument, it employs multivariate regression analysis of observational data and survey experiments. It consists of four papers. The first paper answers the question of why do some countries generate more refugees than others. Previous research has focused on the role of geographical, political, and economic determinants, and little attention has been paid to civil conflict dynamics. This paper examines how a host country s support for rebel groups affects the number of refugees that they accommodate. Countries that support rebels host a higher number of refugees than others, as accommodating refugees can be the continuation of that support and help rebel groups in their armed struggle. Analysis of refugee flows between 1951 and 2011 suggests that countries that support rebel groups host twice as many refugees as others. Results are robust to various model specifications, two different sources for the main explanatory variable, matching analysis, and additional checks. Findings of this article highlight the importance of conflict dynamics in explaining the variation in refugee flows The second paper is interested in different causes of internal and external displacement. While existing studies examine the causes of displacement in general, there is limited research on varying determinants of internal and external displacement. This paper argues that the effect of violence on displacement as a function of perpetrator and geography (i.e., how spread it is). Increases in government violence increase the number of refugees because to escape government violence, people may have to cross an international border as governments are generally effective everywhere within their borders. On the other hand, rebel group activities are limited to a certain area and by leaving the conflict zone, civilians can be free from rebel violence. However, the spread of violence determines the decision to flee. If it is limited to a small region, people can escape from that area within the country and rebel violence increases the number of IDPs. If it is widespread, civilians may not have many opportunities within the country and have to move abroad. Therefore, the effect of rebel violence on internal displacement follows a reverse U-shape. The analysis of refugee and IDPs flows between 1989 and 2017 supports the main arguments and the results are robust to different model specifications and additional checks. The third paper is co-authored with Sigrid Weber and it provides individual-level evidence on flight decisions in light of violence with a conjoint experiment in Turkey. The results suggest that intense indiscriminate violence nearby forces individuals into the decision to leave. In contrast to previous studies, this study finds that persistent violent threats play a more important role in flight decisions than the frequency of attacks. The experiment reveals that violence committed by the government makes a decision to flee abroad more likely than rebel violence, which is complementary to the previous chapter, and that individuals with support networks abroad are less responsive to patterns of violence, making flight decisions under less pressure than individuals without available coping mechanisms elsewhere. These findings contribute to the growing literature on forced migration with individual-level evidence on flight reactions to violence. The final paper shifts focus from forced migration flows to attitudes toward refugees. Previous studies have mainly focused on attitudes in developed countries, which has resulted in a lack of focus on factors prevalent in developing countries but not developed ones. This paper analyzes the effect of transnational ethnic relations and security concerns through a conjoint experiment in Turkey. The results suggest that when there are ethnic tensions in the host country, natives from the majority dominant group have more negative attitudes toward refugees from the minority ethnic group compared to those without any ethnic relations. Security concerns and existing negative intergroup relations are two possible explanations for this effect, and further analysis points to negative intergroup relations as the main mechanism. Additionally, refugees coming from areas controlled by insurgents that have ties to rebels in the host country are less favored than others because refugees might be perceived as a pool of resources for the insurgents. Examining how ethnic relations and security concerns shape attitudes toward refugees has important implications in understanding the externalities of refugee inflows on the host countries.
APPROVED
Keywords: displacement, refugees, civil conflict, violence